848 Cannulated Screws vs DHS Fixation for Undisplaced Intracapsular Neck of Femur Fractures. (19th August 2022) - Fitzpatrick, N; Lynch-Wong, M
Abstract: Introduction: The FAITH RCT (Lancet 2017) described the results of cannulated screws (CS) vs dynamic hip screw (DHS) fixation for undisplaced intracapsular NOF fractures in 1108 patients. Data compared reoperation rates, 24-month mortality and progression to avascular necrosis (AVN). Via retrospective analysis of data from 2018–2020 NHFD, we aimed to compare local outcomes over a 3-year period. Method: Data was collected from NHFD, retrospectively analysed from the past 3 years. 93 patients were included, having undergone CS or DHS fixation for an undisplaced intracapsular NOF fracture. Data comparing length of hospital stay, reoperation rate and progression to AVN were compared. Results: FAITH described reoperation rates of 20% for DHS fixation vs 22% for CS fixation. Data from the last 3 years suggests a reoperation rate of 0% in the DHS cohort vs 6.89% with CS. Locally, there was a 24-month mortality of 21% vs 14% in the study population. Those undergoing CS fixation had an acute inpatient stay of just 8.72 days vs 10.55 days in DHS patients, likely reflecting the less invasive nature of the former. No reports of avascular necrosis were reported locally, compared to 7% in the FAITH trial. Conclusions: Cannulated screw fixation leads to shorter inpatient stays and had no higher incidence on AVN in those included in the study. Whilst it had a higher 24-month mortality, the study did not adjust for confounding variables such as concomitant injury. Locally, reoperation rates were lower than the FAITH trial suggested, as were rates of AVN.